REVIEW OF PUBLIC HOSPITAL BALANCE SCORECARD AND ITS APPLICABILITY TO INDONESIAN PUBLIC HOSPITALS - Saipul Arni Muhsyaf; Masaaki Aoki (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2018)
Indonesia is currently adopting the Balanced Scorecard (BSC) concept for its national health development plan. This indicates that Indonesian health institutions, including hospitals, were encouraged to apply BSC as their strategic management tool. This study is aimed to fill the literature gap by reviewing the existing international experiences regarding the Balanced Scorecard implementation in hospitals and assess its applicability in Indonesian public hospitals. By using a research method called "systematic review", we study in more detail the diversity of proposed BSC for healthcare organizations described from major online-based research databases, e.g. Pubmed, EBSCOhost, Scopus, Emerald, Wiley, ScienceDirect, JSTOR, SpringerLink, and Inderscience.Most of studies on BSC adoption and implementation highlight benefits such as managerial focus improvement, capturing a balanced view of financial and non-financial performance indicators, helpful in goals congruence, useful as cultural and motivational tool, and also for catalyzing changes needed by hospitals. However, time-consuming and a need for intensive exercises were reported as major challenges in its adoption and implementation process. A gradual approach would be an appropriate for Indonesian context, with an institutional assessment of cultural readiness as an additional approach, then followed by the designing, piloting, and gradual scaling-up. Rencana pembangunan di bidang kesehatansaat ini di Indonesia mengadopsi konsep Balanced Scorecard (BSC). Hal ini mengindikasikan bahwasanya institusi-institusi kesehatan, termasuk rumah sakit, juga diharapkan untuk menerapkan konsep BSC tersebut. Studi ini bertujuan untuk mereviu penerapan BSC di rumah sakit di berbagai Negara dan menilai kelayakan penerapannya untuk rumah sakit–rumah sakit di Indonesia. Studi ini menggunakan metode systematic review, yaitu dengan mempelajari artikel-artikel penelitian terkait BSC Rumah Sakit yang dipublikasikan secara online di Pubmed, EBSCO, Emerald, Wiley, Science Direct, JSTOR, Springer Link, dan Inderscience. Studi ini menemukan bahwa manfaat dari penerapan BSC di rumah sakit antara lain meningkatkan focus dalam proses pengelolan institusi, menyeimbangkan capaian kinerja keuangan dan non-keuangan, membantu menyelaraskan tujuan, mendorong budaya kerja yang positif dan meningkatkan motivasi kerja, serta mendorong perubahan lingkungan kerja seseuai kebutuhan rumah sakit. Studi ini juga menemukan bahwasanya tantangan utama dalam penerapan BSC di rumah sakit adalah lamanya waktu yang dibutuhkan untuk proses adopsi dan penerapannya, dan membutuhkan proses percobaan (piloting) yang intensif. Bagi rumah sakit di Indonesia, BSC sebaiknya diadopsi dan diterapkan secara bertahap. Rumah sakit juga perlu melakukan penilaian kesiapan secara kelembagaan (readiness assessment) sebelum dilakukan desain, piloting, dan penerapannya secara bertahap untuk skala yang lebih luas.Keywords:balanced scorecard, systematic review, strategic management tool, management control, benchmarking